Reconciling Mosques: Antagonistic Tolerance and Conflict Management among Religious Groups in East Indonesia - Suprapto, Suprapto (Journal of Al-Tamaddun, 2025)
The use of mosques as public spaces is not immune to contestation and conflict. Various Islamic denominations vie for control over God's house and seek to impose their religious practices. This article draws from field research conducted in Lombok, Indonesia, which has over a thousand mosques. The study focuses on the factors, processes, and management of conflicts within mosques. In-depth interviews with mosque superintendents, religious leaders, societal leaders, and congregants shed light on the issue. The research suggests that some mosque-based conflicts can be resolved through accommodation, tolerance, and compromise. Mosque superintendents can promote peace-building in their communities daily by utilizing win-win solutions. However, conflicts involving Puritan transnational Islamic groups and groups perceived as deviant are particularly challenging and can lead to social segregation. These minority groups are often viewed as less tolerant and a threat to the majority's long-standing religious traditions. On the other hand, collaboration and solidarity between superintendents and congregants of a mosque can help protect it from occupation by transnational Islamic groups and foster a sense of community among the majority Islamic group. The relationship between majority and minority Islamic denominations is often marked by antagonistic tolerance and communal tolerance.